(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
This article analyzes the main theories of the origin of language, ranging from ancient religious and mythological interpretations to modern evolutionary-anthropological approaches. It also discusses the essence of major linguistic schools such as structural linguistics, generative grammar, psycholinguistics, sociolinguistics, and cognitive linguistics. Special attention is paid to the role of corpus linguistics, digital technologies, and AI-based research in 21st-century linguistics. The conclusions highlight current development trends in linguistics and outline the prospects of Uzbek linguistics in the global scientific arena.